2019
DOI: 10.1093/jisesa/iez081
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Utilization in the Regulation of Chitin Synthesis in Brown Planthopper

Abstract: Glucose-6-phosphatase (G6Pase) and hexokinase (HK) are two key enzymes in the glycolysis and gluconeogenesis pathways, which catalyze the synthesis and degradation of glucose in insects, respectively. G6Pase and HK play an important role in insect growth by regulating the metabolism of glucose, leading to the efficient metabolism of other macromolecules. However, it is unclear whether these genes could be investigated for pest control through their actions on chitin metabolism. We studied the potential functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…Trehalose is the first gene in the chitin biosynthesis pathway of insects, which regulates chitin synthase (Zhao et al, 2016;Tang et al, 2017). Previous studies have shown that the inhibition of CHS gene expression will lead to a decrease in the content of chitin, abnormal phenotypes and an increase in mortality of N. lugens (Yang et al, 2017;Li et al, 2017;Pan et al, 2019). Our results showed a decrease or a significant decrease in TRE expression after dsGSK-3 injection (Figure 4A).…”
Section: Discussionsupporting
confidence: 61%
“…Trehalose is the first gene in the chitin biosynthesis pathway of insects, which regulates chitin synthase (Zhao et al, 2016;Tang et al, 2017). Previous studies have shown that the inhibition of CHS gene expression will lead to a decrease in the content of chitin, abnormal phenotypes and an increase in mortality of N. lugens (Yang et al, 2017;Li et al, 2017;Pan et al, 2019). Our results showed a decrease or a significant decrease in TRE expression after dsGSK-3 injection (Figure 4A).…”
Section: Discussionsupporting
confidence: 61%
“…Both autophagy and glycolysis have been reported to be associated with regulation of glucose metabolism during cell starvation [25,26] . During cerebral ischemia/ reperfusion, Reactive Oxygen Species (ROS) overproduction causes oxidative damage to key proteins of glycolysis and ATP synthase, leading to decreased ATP causes many changes in brain function, such as altered membrane potential and increased intracellular Ca 2+ levels, producing detrimental effects on cell function and survival [27] .…”
Section: Resultsmentioning
confidence: 99%
“…However, this enzyme is not present in most insect species, including D. citri. Though present in N. lugens, RNAi studies showed that knockdown of G6Pase in N. lugens had no effect on the genes involved in trehalose metabolism [64].…”
Section: Enzymes Of Gluconeogenesismentioning
confidence: 98%